Impact of Tax Consultant Service Quality and Tax System on Taxpayer Compliance, Moderated By Sanctions - Samsiah Samsiah; Acep Komara; Irwan S. Wahdiat (International Journal Labs, 2026)
Taxpayer compliance remains a critical challenge in Indonesia’s tax revenue optimization, despite ongoing reforms in administration and enforcement. Corporate taxpayers often face complexities in the self-assessment system, leading to reliance on professional tax consultants. However, the interplay between consultant service quality, the tax administration system, and the role of sanctions in shaping compliance behavior has not been comprehensively examined, particularly in regional contexts. This research aims to analyze the influence of tax consultant service quality and the tax administration system on taxpayer compliance, with tax sanctions as a moderating variable. The research employs a quantitative approach using primary data collected from 106 corporate taxpayers registered at the Samsiah Tax Consultant Office in Cirebon, West Java, selected through saturation sampling. Data were analyzed using descriptive statistics, classical assumption tests, multiple linear regression, and Moderated Regression Analysis (MRA) via SPSS. The findings reveal that tax consultant service quality, the tax administration system, and tax sanctions each have a positive and significant direct effect on taxpayer compliance. Improvements in administrative systems and consultant professionalism significantly reduce the compliance burden and enhance adherence to tax regulations. However, the moderation test indicates that tax sanctions do not moderate the relationship between service quality or the administration system and taxpayer compliance. This study concludes that while tax sanctions function effectively as an independent deterrent, enhancing the quality of consultant services and the efficiency of the tax administration system should be prioritized as primary strategies for improving taxpayer compliance. The findings provide theoretical contributions to the attribution and deterrence frameworks and offer practical implications for tax authorities and consultants in designing targeted compliance interventions.